The effect of medicinal herb on fat deposition, meat composition, amino acid and fatty acid composition of broiler meats - Santoso, U.; Fenita, Y.; Kususiyah, K.; Widiantoro, O.; Kadarsih, S. (Diponegoro University, 2018)
The present study was conducted to evaluate the effect of medicinal herbinclusion on fat deposition, chemical composition, amino acid and fatty acid ofbroiler meats. One hundred-sixty eight female broiler chickens aged 15 days were distributed into 7groups as follows: 1) broilers were fed a diet with no medicinal herb as the control (P0) 2) broilers were fed a diet with 5% Sauropus androgynus leaf powder (P1); 3) broilers were fed a diet with 5% bay leaf powder (P2); 4) broilers were fed a diet with 5% basil leaf powder (P3) 5) broilers were fed a diet with 5% papaya leaf powder (P4); 6) broilers were fed a diet with 5% Moringaleaf powder (P5) and; 7) broilers were fed a diet with 5% noni fruit powder. Experimental results showed that the inclusion of medicinal herbs significantly increased protein (P<0.01), iron(P<0.05), kalium, calcium, phosphorus, linolenic acid(P<0.01), methionine, omega 3 unsaturated fatty acid (P<0.05), but significantly reduced fat (P<0.01), glutamic acid, alanine, lignoceric acid, oleci acid (P<0.01) and omega 9 unsaturated fatty acid (P<0.05). It was concluded that Sauropus androgynus leaf was the most effectiveto produce low fat-high protein and mineral meats.